Gender interactions in the academic activity of students of psychology: revelations from the systems - RED 'theory - Dillon Pérez, Francisco Xavier (2019)
The present investigation corresponds to a quantitative approach, of transversal cut and exploratory - descriptive scope. The methodological category of Niklas Luhman's social system and the descriptive tool of network theory are used. Participants correspond to 34 students, 25 women and 9 men aged between 17 and 22 years. The instrument used is INTRED1, validated in two phases. GEPHI software was used for data processing. The objective of the study is to determine the forms of interaction of gender in academic activity, taking as reference the academic performance of the subject of Language and Communication in the Psychology career at a private university in the city of Quito. Among the most important results is that in the network, interactions in academic activity are significantly marked by women.